NEW PROARTICULATA FROM THE VENDIAN OF THE ARKHANGEL'SK REGION - Ivantsov A.Yu. (My University, 2004)
The new taxa Vendia rachiata sp. nov. and Cyanorus singularis gen. et sp. nov. are described from the Upper Vendian of the Onega Peninsula, Arkhangel'sk region. These taxa belong to the invertebrate phylum Proarticulata, which became extinct in the Precambrian. The species Vendia janae Ivantsov, 2001 is assigned to the new genus Paravendia based on new data and the results of restudying the holotype of the type species of the genus Vendia Keller. The axial structure of Proarticulata is interpreted as a digestive-distributive system.
Keywords: Proarticulata; Vendian; Arkhangel’sk region; Russia; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский